(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
The purpose of the study is to analyze the practices of semester system master’s program at MRC, Tahachal. Semester system effectiveness and success depend upon its implementation practices. The qualitative case study research design is used in this study. Teachers, students, the assistant campus chief, department heads, and non-teaching personnel involved in this program were the research participants. The research site was MRC, Tahachal. The tools used for gathering information for the study were interviews, general observations, and document analysis. I have used a qualitative methodology to examine and interpret the data, which includes editing, summarizing, organizing, classifying, and drawing conclusions. The study concludes that the current implementation practice of semester system has been partially implemented. Most students don’t continually engage in the teaching and learning process in the classroom. Regarding the semester system program, neither the teachers nor the students are happy. The roles and responsibilities of the department and campus administration have not been carried out to the anticipated level of expectation. The efficacy of the internal assessment system has been lacking. The dean’s office and its duties are not perceived as being more beneficial to the semester system’s implementation. Since the main stakeholders have not actively engaged in the semester system program’s activities, they ought to routinely and cooperatively participate in developing the campus’s teaching and learning environment. Stakeholders generally agree that the semester system is beneficial when applied in its intended spirit.